TRANSFORMING AGRICULTURAL WASTE INTO VALUE-ADDED PRODUCTS: LOCAL AGROPRENEURSHIP INNOVATION IN SOUTHEAST SULAWESI PROVINCE - Mariani Mariani; Ifin Naim; Anggiat Timbul Aruan; Ryansyah Ramadhan; Muh. Yusril (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Agriculture remains a vital sector supporting the livelihoods of rural communities in Desa Lara, East Kolaka, Southeast Sulawesi Province; however, most farmers still rely on selling raw produce, resulting in low added value and economic vulnerability. This study aims to develop an innovation-based agropreneurship model that transforms agricultural waste—such as rice straw, corn stalks, and peanut shells—into value-added products to enhance farmers’ income and promote sustainable rural economies. Using a quantitative experimental design, data were collected through questionnaires from 50 micro and small enterprises (MSMEs) involved in agricultural activities. Descriptive and inferential statistical analyses, including t-tests and regression, were employed to evaluate the impact of innovation adoption. The results reveal significant improvements in income, innovation capability, and environmental awareness among participants following the implementation of the agropreneurship model. Agricultural waste transformation practices led to an average income increase of 76% and a 46% reduction in open burning, supporting both economic resilience and ecological sustainability. The findings highlight that local innovation and simple technology can effectively strengthen circular economy practices and rural entrepreneurship. This study contributes theoretically by reinforcing the role of agropreneurship in sustainable development and practically by offering a replicable model for community-based innovation and rural economic empowerment.